2022
DOI: 10.1182/bloodadvances.2021005486
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic and transcriptomic analysis in plasmablastic lymphoma identifies disruption of key regulatory pathways

Abstract: Plasmablastic-lymphoma (PBL) represents a clinically heterogeneous subtype of aggressive-B-cell-non-Hodgkin-lymphoma. Although targeted-sequencing-studies and a single-center whole-exome-sequencing (WES) study in HIV+ patients recently revealed several genes, associated with PBL-pathogenesis, the global mutational-landscape and transcriptional-profile of PBL remain elusive. To inform on disease-associated mutational-drivers, mutational-patterns and perturbed pathways in HIV+ and HIV-PBL we performed WES and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 80 publications
(124 reference statements)
0
29
0
Order By: Relevance
“…Several recent studies performing whole-exome sequencings have identified the disruption of several key regulatory pathways including JAK-STAT3, RAS-MAPK and non-canonical NF-kB signaling in PBL [ 30 ]. Gain-of-function JAK/STAT signaling was found in 64% of PBL cases, while RTK-RAS signaling and NF-kB signaling were found in 76% and 58% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies performing whole-exome sequencings have identified the disruption of several key regulatory pathways including JAK-STAT3, RAS-MAPK and non-canonical NF-kB signaling in PBL [ 30 ]. Gain-of-function JAK/STAT signaling was found in 64% of PBL cases, while RTK-RAS signaling and NF-kB signaling were found in 76% and 58% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There also appears to be a difference in mutational landscape based on the EBV status of PBL patients, with EBV- patients having higher mutational and copy-number loads and more frequent TP53 , MYC and CARD11 mutations and EBV+ patients having more mutations that disrupt the JAK-STAT pathway [ 31 ]. MYC status had no correlation with OS or PFS and no bearing on the number of mutations [ 30 ]. Furthermore, there was no correlation between MYC rearrangement and EBV status [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA and RNA were extracted from three 5µm FFPE tissue sections of either tumor or normal tissue (where available; n = 3) employing Maxwell® RSC DNA FFPE kit and Maxwell® RSC RNA FFPE kit (both Promega). WES and RNA-Seq following library preparation using Agilent SureSelect Human All Exon V6 library preparation kit (Agilent Technologies) and NEBNext® UltraT Directional RNA Library Prep Kit (New England BioLabs), respectively were performed on a NovaSeq platform (Illumina) at Novogene (UK) Co. as described 21 . Tumor whole exome libraries were sequenced to a median depth of 119x (mean 129 ± 54 s.d.)…”
Section: Methodsmentioning
confidence: 99%